Epidemiological Determinants of Hypertension Among Menopausal Women: A Case-Control Study on Age and Obesity at Yosomulyo Primary Health Care Center - Eka Refirahmadani; M Ridwan; Gangsar Indah Lestari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Hypertension is a major public health problem that contributes significantly to increased morbidity and mortality, with a higher risk observed among menopausal women due to decreased estrogen levels. In 2023, the prevalence of hypertension in Indonesia reached 30.8%, while in Lampung Province it was reported at 28.45%. In the working area of Yosomulyo Primary Health Center, Metro City, the number of hypertension cases among menopausal women increased from 182 to 244 cases. This study aimed to examine the association of age and obesity with the occurrence of hypertension among menopausal women. A quantitative approach with a case–control design was applied, involving 78 respondents consisting of 39 cases and 39 controls selected through accidental sampling. Age and obesity were defined as independent variables, while hypertension status was the dependent variable. Data were collected through interviews, blood pressure measurements, and anthropometric assessments, and analyzed using the Chi-square test and Odds Ratio. The results indicated a significant association between age and hypertension (p-value = 0.001; OR = 5.570) as well as between obesity and hypertension (p-value = 0.008; OR = 3.918). In conclusion, age and obesity are significantly associated with the incidence of hypertension among menopausal women, highlighting the need for strengthened health education, early hypertension screening, and promotion of healthy lifestyle behaviors as preventive measures.